Magnitude and Determinants of Dental Anxiety among Adult Patients Attending Public Dental Clinics in Dar-Es-Salaam, Tanzania - Kauther Musalam; Karpal S. Sohal; Sira S. Owibingire; Baraka Kileo (International Journal of Dentistry, 2021)
Introduction. It is estimated that, about 40% of the population suffer from dental anxiety. Dental anxiety is considered to be complex and multifactorial with a wide range of provoking factors which may be patient, provider, or environment-related. Aim. This study aimed to assess the magnitude and determinants of dental anxiety among adult patients attending public dental clinics in Dar es Salaam, Tanzania. Methodology. This was a descriptive cross-sectional study carried out in 4 public hospitals in Dar es Salaam, Tanzania. It included 300 adult patients who had dental caries, periodontal diseases, or dental trauma. Data were collected using a self-administered Modified Dental Anxiety Scale (MDAS) questionnaire. Data were analyzed using the SPSS computer software version 23. A one-way Analysis of Variance (ANOVA) was used to assess the association between variables, and the significance level was set at p<0.05. Results. The mean age of participants was 32.18 years (±11.06 SD) with a male-to-female ratio of 1 : 1.43. The means MDAS score was 12.84 ± 4.99. Tooth extraction had the highest mean MDAS score. The majority (261, 87%) of participants had mild-to-severe anxiety. The most common (72.2%) anxiety-provoking factor was an unsympathetic dentist; others included unawareness of the procedure to be carried out (58.3%) and the presence of apprehensive patients (52.0%). The level of anxiety was found to be statistically significantly associated (p<0.05) with young age [p=0.009, AOR 3.06 (95% CI, 1.32, 7.09), female patients [p<0.001, AOR 4.45 (95% CI, 2.05, 9.70)], and a higher education level [p<0.05, AOR 2.32 (95% CI, 1.03, 5.25)]. Conclusion. The prevalence of dental anxiety was high among the participants of this study. Female gender, young age, and a higher level of education constituted determinants of dental anxiety. An unsympathetic practitioner, unawareness of the procedure, and presence of apprehensive patients were the common anxiety-provoking factors.